All iguana families with the exception of basilisks share sex chromosomes - Altmanová, Marie; Rovatsos, Michail; Johnson Pokorná, Martina; Veselý, Milan; Wagner, Florian; Kratochvíl, Lukáš (Zoology (Jena, Germany), 2018)
Once believed to be restricted only to endotherms (mammals and birds), several poikilothermic amniote lineages have recently been documented to possess long-term evolutionary stability in their sex chromosomes. However, many important lineages were not included in these tests. Previously, based on molecular evidence, we documented the homology of well-differentiated sex chromosomes among seven families of iguanas (Pleurodonta), with basilisks (Corytophanidae) being the only exception, as the tested genes linked to X, but missing on the Y chromosome, in other iguanas were autosomal or pseudoautosomal in basilisks. In this study, we test the homology of sex chromosomes in the remaining, previously unstudied iguana families (Hoplocercidae, Leiosauridae, Liolaemidae, Polychrotidae) and in the basilisk genus Corytophanes. Our results show that 12 currently recognized families of iguanas share X-specific gene content conserved from the common ancestor living in the Cretaceous period. However, the results in the genus Corytophanes indicate the loss of the ancestral differentiated sex chromosomes from the ancestor of basilisks. Our new data further confirm the extensive stability of sex chromosomes in iguanas, thus enabling molecular sexing based on the comparison of the number of X-specific genes by quantitative PCR (qPCR) in all but one family of this widely diversified clade.
Keywords: leguáni; qPCR; Sex Chromosomes; fylogeneze; Dedifferentiation; chromozom X; X-linked genes; pohlavní chromozomy; ženské pohlaví; Iguanas; Real-Time Polymerase Chain Reaction; Karyotype; mužské pohlaví; Evolution; Animals; Sex chromosomes; Gene Dosage; genová dávka; kvantitativní polymerázová řetězová reakce; X Chromosome; karyotyp; Female; Phylogeny; Male; zvířata